Chitosan bis(halophenylcarbamate)-(isobutyrylamide) based chiral stationary phases for enantiomeric separation. (12th October 2016) - Tang, Sheng; Bin, Qin; Feng, Zi-Wei; Chen, Wei; Huang, Shao-Hua; Bai, Zheng-Wu
Abstract : Chiral separation materials based on N -isobutyrylated chitosan derivatives with a halogen substituent were prepared and applied for enantiomeric separation. Abstract : The goal of the present study is to systematically investigate the enantioseparation performance and eluent tolerance of chiral stationary phases (CSPs) derived from chitosan bis(halophenylcarbamate)-(isobutyrylamide)s. Hence, N -isobutyrylated chitosan was prepared from completely deacetylated chitosan with a high molecular weight. The N -isobutyrylated chitosan was further derivatized with various halo-substituted phenyl isocyanates, consequently affording a series of chitosan bis(halophenylcarbamate)-(isobutyrylamide)s, which were coated onto 3-aminopropyl silica particles to obtain a class of CSPs. The chiral recognition ability of these CSPs was evaluated with nineteen racemates. It was found that the chitosan bis(halophenylcarbamate)-(isobutyrylamide)s showed powerful enantioseparation performance, and those with 4-chlorophenylcarbamate, 3, 4-dichlorophenylcarbamate and 4-trifluoromethoxyphenylcarbamate seemed to exhibit comparable or even more superior enantioseparation ability for the tested racemates in comparison with the well-known derivatives of cellulose and amylose. In addition, the dissolvability and swelling of the prepared chitosan bis(halophenylcarbamate)-(isobutyrylamide)s in organic solvents were discussed in particular. The eluent tolerance of the CSP prepared from chitosan bis(3, 4-dichlorophenylcarbamate)-(isobutyrylamide), which exhibited relatively more favorable enantioseparation performance among the prepared CSPs, was investigated. It was observed that the tested CSP could be analyzed with 100% ethyl acetate, 100% chloroform and n -hexane/THF (70/30, volume ratio) without a significant loss of recognition and enantioseparation ability. As a consequence, we can safely draw the conclusion that chitosan bis(halophenylcarbamate)-(isobutyrylamide)s prepared from chitosan with a high molecular weight can show good enantioseparation performance as well as satisfactory eluent tolerance.